Disparity of Bladder Cancer Incidence Among Male Workers Across Industries: A Population Based Cohort Study From South Korea. - Jae Yoon Kim; Jin-Ha Yoon; Ki-Bong Yoo; Woo-Ri Lee; Wanhyung Lee; Mo-Yeol Kang (Journal of Occupational & Environmental Medicine, 2023)
Background: This study aimed to investigate the bladder cancer risk across workers' industries. Methods: This study was conducted using Korean National Health Insurance claims data. Workers were included in this study to build a retrospective cohort of the entire working population. Workers' industries were divided into 77 industries according to the Korean Standard Industry Classification division category. The standardized incidence ratio was calculated by comparing 77 industries according to the Korean Standard Industry Classification with the educational public officer. Results: Bladder cancer risk was particularly high in the following industrial sectors: passenger land transport, except transport via railways; sea and coastal water transport; restaurants and mobile food service activities; telecommunications; and computer programming, consultancy, and related activities. Conclusions: Our result provides evidence regarding the disparity of bladder cancer incidence among male workers across industries.